Akibat Hukum Pencairan Kredit Fiktif Dengan Menggunakan Covernote (Studi kasus putusan Pengadilan Negeri Pangkal Pinang Nomor 21/Pid.sus Tpk/2021/PN PGP) - Syahida, Jeri Gunarko; Fendri, Azmi; Syam, Misnar (Dinasti Research, 2025)
Covernotes are not regulated by the Notary Position Law (UUJN), so as a result of the existence of a covernote general legal provisions apply, both civil and criminal. Covernotes can be considered not included as authentic deeds because they are not regulated and stipulated in statutory regulations. Covernotes are not regulated by the Notary Position Law (UUJN), so as a result of the existence of a covernote general legal provisions apply, both civil and criminal. Covernotes can be considered not included as authentic deeds because they are not regulated and stipulated in statutory regulations. 1) The legal position of notary covernotes in credit agreements: covernotes should not be used as a basis for credit disbursement because covernotes are basically only temporary collateral. In most cases, the covernote made by the notary only serves as proof that the certification process is still ongoing. Covernote does not have a legal umbrella because it is not regulated in the laws and regulations, either the Banking Law or UUJN. As a result, criminally applicable legal provisions will apply. 2) The judge saw that the charges against the defendant notary Gemara Handawuri were based on Article 3 of the Law of the Republic of Indonesia Number 31 of 1999 concerning the Eradication of Corruption Crimes, which states that the violations committed constitute a criminal act of corruption. The judge has decided to sentence notary Gemara Handawuri based on the testimony of the defendant, witnesses and evidence that provides conviction. 3) The creditor does not know how long the Cover Note will last, so there is no confidence in how long the certificate will last.